2004
DOI: 10.1002/ajmg.c.30002
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of a multistate study of congenital hearing loss: Preliminary data from Utah newborn screening

Abstract: A multistate Centers for Disease Control and Prevention (CDC) study was designed to investigate the etiology of congenital hearing loss in infants ascertained through state-mandated hearing screening or early hearing loss detection and intervention (EHDI) programs. At least 50% of permanent childhood-onset hearing loss is due to genetic causes, and approximately 20% of all infants with congenital hearing loss have mutations in the GJB2 gene. Another 1% of childhood hearing loss is due to mitochondrial DNA (mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…2 A number of states have made these residual bloodspots available for biomedical and environmental research for a broad range of projects. [3][4][5][6] The storage and use of residual specimens for research have become controversial, primarily because of public concerns over the lack of parental awareness and consent. 7 Research demonstrates that parents are poorly informed about NBS programs in general, even when conducted with permission, and are largely unfamiliar with the practice of many health departments to retain and use residual bloodspots.…”
Section: Discussionmentioning
confidence: 99%
“…2 A number of states have made these residual bloodspots available for biomedical and environmental research for a broad range of projects. [3][4][5][6] The storage and use of residual specimens for research have become controversial, primarily because of public concerns over the lack of parental awareness and consent. 7 Research demonstrates that parents are poorly informed about NBS programs in general, even when conducted with permission, and are largely unfamiliar with the practice of many health departments to retain and use residual bloodspots.…”
Section: Discussionmentioning
confidence: 99%
“…27 The second screened 25 neonates that had altered otoacoustic emissions tests, among which the mutation was not found. 28 Screening of 300 neonates in Argentina and in 712 normal-hearing subjects did not detect the A1555G mutation. 29 These studies have reported Chart 1.…”
Section: Discussionmentioning
confidence: 95%
“…12 Although the number of cases in both groups was different from the number in some published studies, and although the mutation was not found in both groups (HLG and control groups), we were able to confirm the results of studies that also did not find the mutation in non-Asian or Arab ethnic groups. [24][25][26][27][28][29] There is a single study in Brazil reporting the findings of five families with hearing loss cases in which the prevalence of the mutation was 2% (4 cases). Only one of these positive cases was associated with an assumed aminoglycoside exposure; no mutation was found in the control group composed by black, white or Asian (Japanese or Chinese) ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Infants in this group need careful clinical genetic evaluations to evaluate for the possibility of a syndromic diagnosis 25 as well a follow-up studies based on the differential diagnosis outlined earlier and as recommended by the American College of Medical Genetics. 29 Current protocols suggest a workup that includes CT scanning for cochlear and vestibular anomalies, studies to determine prenatal infections such as the toxoplasmosis, rubella, cytomegalovirus, herpes virus, and syphilis, renal ultrasound, urine analysis, electrocardiogram, thyroid studies, and ophthalmological surveillance.…”
Section: Ehdi and Genetic Testingmentioning
confidence: 99%
“…Knowing the GJB2/GJB6 mutation status at the outset in a child with hearing impairment will save the time, effort and cost involved with performing electrocardiograms, serial ophthalmological evaluations, renal ultrasounds, urine testing, and complicated thyroid studies. 25 Because GJB2/GJB6 genetic testing offers clinical and informational benefits, it is a near certainty that it will become an important addition to current EDHI protocols. In this commentary, we discuss issues to be considered before there is widespread inclusion of genetic testing into the EHDI process, incorporating some of our experience from our current study on the impact of genetic testing for hearing impairment on individuals and families as part of the EHDI process.…”
mentioning
confidence: 99%